Optimal regulation under imperfect enforcement: Permits, tickets, or both?. (6th February 2020) - Samuel, Andrew; Farmer, Amy; Mendez, Fabio
Abstract: Economic activity is often regulated through both permits and tickets (subsequent inspections). We study the effectiveness of such policies where corruption and an underground economy make enforcement imperfect. In the theoretical model, asymmetric information justifies regulatory action which is enforced by corruptible bureaucrats. We find that regulation through permits alone is useless when corruption exists, while tickets still offer some benefit. Surprisingly, we also find that a system with both permits and tickets achieves welfare that is higher than that which can be achieved with only tickets—that combining the two mechanisms has an effect that is greater than the "sum of the parts."